Using 3D-Printing for Improving Backorder Recovery - A study performed at Volvo Group - Almqvist, Elise; Corin, Carolina (My University, 2016)
Purpose – Fast backorder recovery for spare parts is crucial for customer satisfaction but is sometimes slow due to sourcing or tooling issues, long production- or waiting time. 3D-printing has the potential to complement and improve Volvo’s current backorder recovery process. Therefore, the purpose of the thesis is to assess the possibility to use 3D-printing for backorder recovery where it is beneficial in terms of cost, lead time and environmental impact. Scope - The expected outcome is to provide a recommendation of direction of how 3D-printing can be used as complement in Volvo’s backorder recovery process. The recommendation is of a conceptual nature of how 3D-printing can become a part of the Volvo’s way of working with backorders. The proposal includes what can be achieved today and in five to ten years if the rapid development of 3D-printing technologies continues. The thesis has a logistics focus and the scope is to see when and how 3D-printing can be used in order to improve backorder recovery, i.e. it is not used how backorders can be avoided. Methodology – The thesis is of qualitative nature, where the empirical findings are compared to relevant literature in order to answer the research questions. To get a reliable result both first and secondary data has been collected. The data was analyzed in order to provide a future recommendation for in what direction the company should go in the investigated area. Additionally, a case study was performed to illustrate an actual case and to see if the analyzed parameters affected the chosen measurements. Results – One precondition today is long time backorders due to the lead time of 3D-printing. The case study result shows that today lead time can be shortened for these backorders, but at the expense of increased cost. However, the application has been noticed to be very case dependent and therefore difficult to generalize. Today’s major limitations, which are lack of quality assurance, lead time and product printability, are however believed to diminish in the future and increase the potential further for backorder recovery. Conclusion – The conclusion from the investigation is that backorder recovery is an area with high potential for using 3D-printing. Even if today 3D-printing as a technology is not quite mature to apply in the backorder recovery process.
Keywords: Transport; Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics